Effects of Transition Metal Doping to Cerium-Oxides in Thermal Reduction Reaction. Issue 1 (April 2020) - Nishimura, Takaki; Tsutsumi, Yuki; Ishii, Tomohiko; Kodama, Tatsuya; Sakane, Genta
Abstract: Considering our lives, novel energy production is so required, and many scientists have been investigated this problem from a lot of views. One of the ways for the new energy productions is the solar power thermochemical production by an oxidation-reduction reaction of the ceramics CeO2 (ceria). In this research, the ceria is used for obtaining an H2 gas in vapor reaction in high-temperature thermal equipment which has a heat production system consisting by focused sun light. Nowadays technology has been also developed to keep a human living, not to harm the Earth environment. From these points, it is realized that how important the H2 gas is for our lives, so we are trying to improve the thermochemical H2 gas production by means of a ceria as a catalyst. Our purpose in this study is, to point out what effects occur in doped ceria's thermal reduction (TR) reaction by using DV-Xα method. Comparing the models between the pure ceria and the Mn doped ceria, we have realized the difference by the reaction. In this appearance, one of the considerations is a view from p-DOSs (partial-Density of States), in which there are different O-2p DOSs by different crystal structures. From this view, we considered that the ceria structure would become more stable to keep the stable cyclic thermal reaction in Mn doped ceria.